Transthoracic versus transhiatal esophagectomy - Łochowski, Mariusz; Pryt, Łukasz; Brzeziński, Daniel; Kozak, Józef (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Aim of the study : The aim of the present study is to compare patient qualification and treatment results for esophageal/cardia carcinoma patients treated with open transthoracic esophagectomy (TTE; McKeown) and with transhiatal esophagectomy (THE; Orringer). Material and methods : We analyzed a group of 102 patients (24 women; 78 men; mean age 59.5 years) who underwent surgery for esophageal/cardia cancer in the years 2007-2011. We performed 38 transthoracic esophagectomies (TTE) and 64 transhiatal esophagectomies (THE). In all the cases, the conduit made from the stomach was moved through the posterior mediastinum and a two-field lymphadenectomy was performed with cervical anastomosis (employing the Collard method). Additionally, nutritional support was provided preoperatively (depending on the nutritional status of the patient) and postoperatively (to all patients). Results: Patients qualified for TTE were at higher TNM stages of the disease, had tumors located in the proximal part of the esophagus, and had more concomitant diseases. The tumors were usually squamous cell carcinomas. For THE we qualified patients with lower TNM stages. The tumors were located closer to the cardia and were usually adenocarcinomas. We observed a higher volume of perioperative blood loss among the TTE group, who also required mechanical ventilation more frequently. Contrarily, in the THE group there were more intraoperative arrhythmias, postoperative pneumothoraces, and pleural effusions. We revealed no relationship between anastomotic leaks and operation type. Rather, they were related to malnutrition (albumin level). Anastomotic stenosis (stricture) was more frequent among the THE patients. Mean operative time was reduced in the THE group (150 min) as compared to the TTE group (180 min). Conclusions: 1. Selecting the operative method for esophageal/cardia cancer patients depends on the stage of the disease and the location of the tumor. 2. Transhiatal operations are shorter in duration and put less strain on the patient, while transthoracic operations are characterized by increased blood loss. However, the complication and mortality rates are similar for both procedures.